Prosedur Penanganan Dokumen Manifes Muatan Curah Cair (Palm Oil Product) Kapal MT. Blue Phoenix oleh PT. Seroja Jaya - M Aldi Ramadhan; Suratni Ginting; Meriah Kita Deliani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Manifest is a list of cargo contents carried by a ship, which contains the type of goods, cargo number, sender's name and recipient's address at the destination port also called a bill of lading. When handling manifest documents in the shipping world, it requires the issuance of manifests as a condition for transporting goods and the obstacle is that the cargo shrinks too much during ullage so that the final result of the load causes delays in processing manifest documents. In the research paper made by the author using the field method (Field Search) and also with the research method of library study (Library Study) obtained from references from the library of the Indonesian Maritime Polytechnic Adiguna Medan (Poltek AMI) the purpose of writing this paper is to find out how to handle liquid bulk cargo manifest documents. As well as efforts made so that the handling of manifest documents runs with smoothly organized procedures at PT Seroja Jaya Agensi Kuala Tanjung. As for efforts to run smoothly when handling manifest documents, Among them shipping instructions must be sent on time by the Shipper when the ship has not docked and before the ship loads palm oil products at jetty A Multi Nabati Asahan.